Perancangan model bisnis dengan triple layered business model canvas untuk pengembangan UMKM Kecap Segi Tiga Majalengka - Hamidah, Siti Nur; Suhendra, Agus Achmad; Martini, Sri (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to design a business model that supports the development strategy of the soy sauce business in UMKM Kecap Segi Tiga Majalengka, using the Triple Layered Business Model Canvas (TLBMC) approach. This research identifies the company's strategic position through SWOT analysis and determines strategy priorities using the Analytical Hierarchy Process (AHP) method. The samples used include owners, managers, production staff, marketing, customers, and representatives of the industrial office. The results of the SWOT analysis show that the Kecap Segi Tiga MSME is in a grow and develop position (quadrant I), which requires a growth strategy. The highest weight in the AHP analysis for the economic layer was found in revenue streams and cost structure (score 0.33297), the environmental layer in functional value and materials (score 0.1890), and the social layer in employee aspects (score 0.2830). This proposed business model is reorganized in the form of TLBMC to support the development of MSMEs.